STUDI POLA PEMANFAATAN RUANG TERBUKA PUBLIK BERDASARKAN LIFESTYLE MAHASISWA DI KAMPUS UNIVERSITAS GAJAHMADA YOGYAKARTA - Wardhani, Apriliana Dyah (Jurnal Tataloka, 2009)
The development is related to various aspects covering political, socio-cultural, technological, economic, and physicalaspects (Yunus, 2000:107). Mutual development of a city indeed influences the development itself. As in Yogyakarta, its role astourism and education destination influences the city development. Urban development, city role, and urbanization are closely relatedwhich then affect the social values of the community. The method used in this study is rationalistic qualitative utilizing thepower of reason as the source of analytical capability in the whole process of the research. This research requires deep and detailanalysis yet thorough and holistic. The result of this study is the pattern of public space based on the lifestyle characteristic of thestudents undergoing development due to social process and influence of westernization and modernization. This proves that based onvalue system, students are open toward foreign culture. Moreover, this influences the activities which prompt them to follow thetrend. Consequently, it affects the demand of space to accommodate their interest to show their existence.